2017
DOI: 10.1136/bmjopen-2017-018705
|View full text |Cite
|
Sign up to set email alerts
|

National citation patterns ofNEJM,The Lancet,JAMAandThe BMJin the lay press: a quantitative content analysis

Abstract: ObjectivesTo analyse the total number of newspaper articles citing the four leading general medical journals and to describe national citation patterns.DesignQuantitative content analysis.Setting/sampleFull text of 22 general newspapers in 14 countries over the period 2008–2015, collected from LexisNexis. The 14 countries have been categorised into four regions: the USA, the UK, Western World (European countries other than the UK, and Australia, New Zealand and Canada) and Rest of the World (other countries).M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 12 publications
2
20
0
1
Order By: Relevance
“…The factors associated with greater levels of newspaper coverage for scientific papers have also been studied. They include the prestige of the journal [ 17 ], the availability of press releases [ 18 22 ], the domestic preference of newspapers for journals from their own country [ 23 ], and the newsworthiness of the topic [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors associated with greater levels of newspaper coverage for scientific papers have also been studied. They include the prestige of the journal [ 17 ], the availability of press releases [ 18 22 ], the domestic preference of newspapers for journals from their own country [ 23 ], and the newsworthiness of the topic [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the current scientific interest in the microbiome, its social impact in newspapers has not been properly analyzed. One relevant way of studying the subject is by analyzing the number of newspaper articles in which authors, papers or journals are cited (called “press citations”) [ 18 , 23 , 30 ]. As such, our first objective was to analyze the extent to which the predictable increase in the number of microbiome papers in recent years has had a parallel impact in the press, in both general and business newspapers, given the potential for harnessing the human microbiome to prevent, diagnose or cure disease.…”
Section: Introductionmentioning
confidence: 99%
“…Citations of medical journals by other journals are important for scientific publications. They are applied to calculate the impact factors of journals, which are viewed as a proxy for the scientific relevance and influence of an academic community [15]. From the TRPM7 paper with the most cited times over the past 15 years, they found that TRPM7 serves as a MLKL (Mixed Lineage Kinase Domain-like) downstream target to mediate Ca 2+ influx and TNF-induced necroptosis, which reveals the critical mechanism of MLKL-mediated necroptosis [16].…”
Section: Intellectual Basementioning
confidence: 99%
“…El valor noticioso de la información es un factor importante pero no es un buen predictor de lo que acaba convirtiéndose en noticia. La publicación de una noticia de biomedicina obedece a una serie de factores, entre los que se cuentan la existencia de una nota de prensa asociada (De-Semir, 1998;Schwartz et al, 2012;Yavchitz et al, 2012;Casino, 2015;Sumner et al, 2016), la relevancia científica de la información (Repiso; Chaparro-Domínguez, 2018) y un factor nacional que prima la difusión de la investigación de un país en los medios nacionales Rius;Cobo, 2017). Pero la lista completa de factores asociados con la cobertura periodística y la importancia relativa de cada uno, en particular el peso de los intereses económicos y profesionales asociados a la información, está lejos de ser comprendida.…”
Section: Conocer El Valor Noticioso De La Biomedicina Y Su Impacto Meunclassified